Independent Predictors of Late Presentation in Patients with ST-Segment Elevation Myocardial Infarction - Rodrigues,Juliane Araujo (2018)
Abstract Background: In patients with acute ST-segment elevation myocardial infarction (STEMI), the time elapsed from symptom onset to receiving medical care is one of the main mortality predictors. Objective: To identify independent predictors of late presentation in patients STEMI representative of daily clinical practice. Methods: All patients admitted with a diagnosis of STEMI in a reference center between December 2009 and November 2014 were evaluated and prospectively followed during hospitalization and for 30 days after discharge. Late presentation was defined as a time interval > 6 hours from chest pain onset until hospital arrival. Multiple logistic regression analysis was used to identify independent predictors of late presentation. Values of p < 0.05 were considered statistically significant. Results: A total of 1,297 patients were included, with a mean age of 60.7 ± 11.6 years, of which 71% were males, 85% Caucasians, 72% had a mean income lower than five minimum wages and 66% had systemic arterial hypertension. The median time of clinical presentation was 3.00 [1.40-5.48] hours, and approximately one-quarter of the patients had a late presentation, with their mortality being significantly higher. The independent predictors of late presentation were Black ethnicity, low income and diabetes mellitus, and a history of previous heart disease was a protective factor. Conclusion: Black ethnicity, low income and diabetes mellitus are independent predictors of late presentation in STEMI. The identification of subgroups of patients prone to late presentation may help to stimulate prevention policies for these high-risk individuals.